(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: The aim of the article is to present and examine the main segments and key objectives of the content of the Schengen Strategy, published by the European Commission on 2 June 2021, occasionally linking and complementing it with other relevant regulations and documents. The European Strategy Paper could be a key document for future Hungarian border management activities. For this reason, it is important and timely to be the first to process it scientifically. Methodology: Document and contents analysis, analysis of statistical sources. Findings: The Schengen Strategy, which is the subject of this article, contains a number of legislative proposals (e.g. amendments to regulations, new draft regulations), which will directly affect Hungary in the future through its EU membership. It is necessary to prepare for this as well as possible, both at the decision-making and the implementation level. In addition, the future implementation of the identified objectives will entail a number of diplomatic, logistical and human resource management tasks, for which it is recommended that adequate preparation is made. The reform of the Schengen evaluation mechanism will also change the practice of Schengen evaluations, which will also require a completely new approach by the bodies and authorities concerned. Value: The document on which the study is based has not been presented in the domestic arena before, so it can be considered as a niche document, its relevance is obvious, as the implementation of the objectives it contains will take place in the coming years. In addition, it can provide useful information and guidance to important domestic, mainly law enforcement authorities and academics.